Migratory grief: a systematic review - Renner, Anna; Schmidt, Viktoria; Kersting, Anette (Frontiers in Psychiatry, 2024)
Introduction Migration is often accompanied by interpersonal, material and abstract losses and can be associated with migratory grief. The correlates of migratory grief have not yet been sufficiently addressed in research. This review aims to systematically investigate the relationship between migratory grief and psychopathology, to map the current state of research on this highly relevant topic and to derive relevant implications for the target group. Method A systematic literature search of electronic databases (PubMed/Medline, PsycINFO, Web of Science) was conducted up until January 2023. Primary empirical quantitative and qualitative studies with migrants were included that assessed the association between migratory grief and psychopathology, using a specific instrument for migratory grief (quantitative) or named migratory grief as relevant topic (qualitative). Studies that only captured aspects of migratory grief, were not written in English, or were descriptive/non-peer-reviewed publications, were excluded. A quality assessment of all studies included was performed using the Mixed Methods Appraisal Tool. The results were synthesized using a narrative synthesis approach. Results All studies (quan. = 4; qual. = 1) were cross-sectional and used convenience samples. The studies had a mean number of 83 participants with a total of N = 487 participants included in the current review. All included studies reported a significant relationship between migratory grief and psychological distress. Discussion Despite the quality of the included studies being limited, our results show that there is a link between migratory grief and depression among refugees and migrants. However, there are only few studies in this currently and certainly also in the future relevant field of research, which is why further studies on factors influencing migratory grief as well as associations with other disorders would be desirable. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier CRD42023403448.